Analisis Perbandingan Baja Profil Pipa dan Baja Profil Double Canal Terhadap Kinerja Struktur Atap Tribun Stadion - Rahmatia Hastanty Kantu; Rifadli Bahsuan; Mirzan Gani (Transbahasa, 2025)
A stadium is a building designed to accommodate various sports activities such as football, athletics, and badminton, requiring a strong and stable structural system. Stadium structures generally use reinforced concrete for main structural elements and steel roof trusses to support spectator stands. In steel roof design, the selection of steel profiles is crucial because it affects structural performance, load capacity, and material efficiency. This study aims to analyze and compare the performance of pipe steel profiles (Hollow Structural Section/HSS) and double channel steel profiles used in stadium stand roof structures. The comparison is based on cross-sectional area, unit weight, nominal strength, and design strength under axial compression and tension loads. The results show that the HSS76.2×4.8 profile, with a cross-sectional area of 1078.16 mm² and a weight of 8.46 kg/m, provides compressive and tensile strengths of 294.08 kN and 329.92 kN, respectively, when used as a diagonal member. The HSS127×7.9 profile, with an area of 2959.95 mm² and a weight of 23.24 kg/m, achieves compressive and tensile strengths of 868.59 kN and 905.74 kN as top and bottom members. In comparison, the 2C75×5.2 double channel profile shows a compressive strength of 326.29 kN and is prone to flexural–torsional buckling, while the 2C150×12.2 profile reaches a compressive strength of 793.44 kN. Overall, pipe steel profiles demonstrate better efficiency under axial loads due to lower weight and smaller cross-sectional area for comparable strength.